TFC: Token Flow Control in Data Center Networks - Zhang, Jiao; Ren, Fengyuan; Shu, Ran; Cheng, Peng (EuroSys, 2016)
Services in modern data center networks pose growing performance demands. However, the widely existed special traffic patterns, such as micro-burst, highly concurrent flows, on-off pattern of flow transmission, exacerbate the performance of transport protocols. In this work, an clean-slate explicit transport control mechanism, called Token Flow Control (TFC), is proposed for data center networks to achieve high link utilization, ultra-low latency, fast convergence, and rare packets dropping. TFC uses tokens to represent the link bandwidth resource and define the concept of effective flows to stand for consumers. The total tokens will be explicitly allocated to each consumer every time slot. TFC excludes in-network buffer space from the flow pipeline and thus achieves zero-queueing. Besides, a packet delay function is added at switches to prevent packets dropping with highly concurrent flows. The performance of TFC is evaluated using both experiments on a small real testbed and large-scale simulations. The results show that TFC achieves high throughput, fast convergence, near zero-queuing and rare packets loss in various scenarios.